2008
DOI: 10.1007/s00244-008-9201-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Sulfate on Growth, Development, and Escape Behavior in Epidalea calamita Embryos and Larvae

Abstract: Epidalea calamita embryos at Gosner stages 3 and 19, and larvae at Gosner stage 25, were exposed to different copper sulfate concentrations, ranging from 0.05 to 0.40 mg Cu L(-1), in 96-h acute toxicity tests. Embryonic and larval mortality, development, growth, and larval escape behavior were evaluated. LC(50) at 96 h obtained at Gosner stages 3, 19, and 25 were 0.22, 0.08, and 0.11 mg Cu L(-1), respectively. Embryonic and larval developments were delayed after 96 h of copper sulfate exposure. Growth was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…Later developmental stages, as would have been present at the time of the late application, were not examined in that study. Similar patterns of lower sensitivity very early in development (Gosner stage 3) compared to later in development (Gosner stages 19 and 25) have been found in the effects of copper sulfate on Bufo calamita tadpoles [6]. Studies conducted later in ontogeny, as in the present study, have found mixed results including increased sensitivity later in ontogeny [5], or similar sensitivity over ontogeny [32].…”
Section: Roundup and Amphibians Over Ontogenysupporting
confidence: 80%
See 1 more Smart Citation
“…Later developmental stages, as would have been present at the time of the late application, were not examined in that study. Similar patterns of lower sensitivity very early in development (Gosner stage 3) compared to later in development (Gosner stages 19 and 25) have been found in the effects of copper sulfate on Bufo calamita tadpoles [6]. Studies conducted later in ontogeny, as in the present study, have found mixed results including increased sensitivity later in ontogeny [5], or similar sensitivity over ontogeny [32].…”
Section: Roundup and Amphibians Over Ontogenysupporting
confidence: 80%
“…By knowing the timing and magnitude of exposures along with the sensitivity of different life stages, we can achieve a much more refined assessment of risk. The importance of ontogenetic sensitivity has received little empirical attention, particularly in amphibians, yet the few studies that have been conducted (assaying only a few pesticides) often demonstrate that sensitivity can change over ontogeny, although there are currently too few studies to identify any predominant patterns in this sensitivity [3][4][5][6]. While it could be argued that the stages most sensitive to pesticides might be early in development or points in ontogeny that experience rapid development (i.e., metamorphosis), it remains unclear whether there are any general patterns among organisms or among pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the idea that suitable terrestrial habitats around breeding ponds are critical for amphibians (Hazell et al 2001). The negative effect of agriculture on amphibian populations has been previously described (Bonin et al 1997;Hecnar and M 0 Closkey 1997;Beja and Alcazar 2003;Peltzer et al 2006) and also the negative effects of toxic substances on population structure (Christin et al 2003;Davidson 2004;Rohr and Crumrine 2005;García-Muñoz et al 2009). Intensification of agriculture is widely recognized as one of the most significant human alterations to the global environment.…”
Section: Discussionsupporting
confidence: 90%
“…More effects have been observed in embryo and larval stages, and Cu sensitivity varies greatly among species [13,14], source locations, clutches [14,17], and developmental stage [18]. Sublethal effects of Cu exposure can be manifest at embryonic [18] or larval [19] stages and can include delayed development [19] or reduced size at metamorphosis [20]. In amphibians, these effects are known to reduce survival and lower female clutch size and thereby limit recruitment into the population [21].…”
Section: Introductionmentioning
confidence: 99%